2021
DOI: 10.3390/app11177891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wood Vinegar Substitutes on Acetic Acid for Coagulating Natural Para Rubber Sheets during the Drying Process

Abstract: The coagulating properties of wood vinegar from para rubber wood, bamboo, and coconut shell used as a substitute for acetic acid in the production process of natural rubber (NR) sheets were investigated and considered. For the dirt and volatile content, the tensile strength at break, the percentage of elongation at break, and the 300% modulus, the results showed that the types of wood vinegar coagulants were not significantly different from acetic acid. However, the Mooney viscosity and plasticity retention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The antifungal performance of the ADS, as a function of ACW content, was measured by the area fractions of fungal growth on the ADS, when the rubber sheets were left at ambient conditions for 5 months. The percentage of fungal growth area was calculated according to Equation (5). It was observed that the dry rubber sheet had a yellow-brown color and was without fungi (white spots on the NR surface) before the storage for 5 months (Figure 8a).…”
Section: Antifungal Performance Of the Rubber Sheetmentioning
confidence: 99%
See 2 more Smart Citations
“…The antifungal performance of the ADS, as a function of ACW content, was measured by the area fractions of fungal growth on the ADS, when the rubber sheets were left at ambient conditions for 5 months. The percentage of fungal growth area was calculated according to Equation (5). It was observed that the dry rubber sheet had a yellow-brown color and was without fungi (white spots on the NR surface) before the storage for 5 months (Figure 8a).…”
Section: Antifungal Performance Of the Rubber Sheetmentioning
confidence: 99%
“…The results showed that vinegar from rubber wood reduced the fungal colony counts on rubber sheets and decreased malodors while drying the rubber [ 4 ]. Recently, wood vinegars from para rubber wood, bamboo, and coconut shell have been tested as substitutes for a commercial acid (i.e., acetic acid) in coagulating rubber [ 5 ]. Regarding the physical and mechanical properties of the NR product, the results showed that the type of wood vinegar coagulant (i.e., para wood, bamboo, or coconut shell vinegar) did not cause significant differences from using the commercial coagulant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After storage about two hours, the slabs were compressed between two rollers and then washed with clean water and hung on bamboo bars before drying at the chamber. In drying process, NR sheets were carried on the chamber which set-up inlet air velocity and the temperature until the final moisture content decreased to 3.0±1.0% dry basis [8,13,24]. In this study, the 0.6 × 0.8 × 1.0 m in size (width × length × height) hot air oven chamber with containing 100 kg of NR sheets was investigated, as shown in Figure 1.…”
Section: Methodology 21 Materialsmentioning
confidence: 99%
“…The color value increased with increasing the drying temperature and drying time. Kalasee and Dangwilailux [24] have been the only ones studying the effects of the chemical and physical properties when coagulating with different acetic acid. Their paper predicts the color changes of the drying and color kinetics of NR sheets during the drying process.…”
Section: Introductionmentioning
confidence: 99%